2008
DOI: 10.3989/cyv.2008.v47.i5.165
|View full text |Cite
|
Sign up to set email alerts
|

Electrodos basados en Perovskita para pilas de combustible SOFC simétricas

Abstract: The use of the same material as anode and cathode in symmetrical solid oxide fuel cells (SFCs) promises notable benefits as easier fabrication, hence lower cost production and resistance to carbon formation upon fuel cracking. Although chromites and chromo-manganites have been proposed as candidate electrode materials for this novel SOFC configuration, demonstrating promising performances, further work is required to develop compositions exhibiting higher efficiencies. In the present work we evaluate the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…[ 110,111 ] It was found that the structure of LSTF evolved from cubic to orthorhombic symmetries with increasing irondoping content, and this transformation accompanied an increase in electrical conductivity. [ 110,111 ] It was found that the structure of LSTF evolved from cubic to orthorhombic symmetries with increasing irondoping content, and this transformation accompanied an increase in electrical conductivity.…”
Section: Srtio 3 -Based Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 110,111 ] It was found that the structure of LSTF evolved from cubic to orthorhombic symmetries with increasing irondoping content, and this transformation accompanied an increase in electrical conductivity. [ 110,111 ] It was found that the structure of LSTF evolved from cubic to orthorhombic symmetries with increasing irondoping content, and this transformation accompanied an increase in electrical conductivity.…”
Section: Srtio 3 -Based Oxidesmentioning
confidence: 99%
“…Canales‐Vázquez et al evaluated the potential application of iron‐doped LST (LSTF) as the electrodes for symmetrical SOFCs . It was found that the structure of LSTF evolved from cubic to orthorhombic symmetries with increasing iron‐doping content, and this transformation accompanied an increase in electrical conductivity.…”
Section: Recent Developments In Electrode Materialsmentioning
confidence: 99%